A new small-flowered Cyrtochilum (Oncidiinae) from Peru - Dalström, Stig (Universidad de Costa Rica, 2022)
A new small-flowered Cyrtochilum from Peru is described, illustrated with photos and drawings, and compared to similar species. The new species is similar to C. fidicularium and C. gracile in having extra thumb-like projections above the rounded ventral lobes of the column but differs from C. fidicularium by the more sharply pointed and forward projecting callus keels on the lip and by a longer front-lobe of the lip, versus blunt and downward directed lobes in C. fidicularium. The new species differs readily from C. gracile by the long and wiry inflorescence, versus a more sub-erect and straighter panicle in C. gracile.